2014
DOI: 10.1016/j.hlc.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis

Abstract: The mean age was 50.5 years. Nine (10.5%) of these patients had Prosthetic Valve Endocarditis, the remaining 76 (89.5%) had Native Valve Endocarditis. Twenty-nine percent of patients were NYHA 4 pre-operatively, 15% of patients were haemodynamically unstable requiring inotropic support, 34% were persistently febrile despite antibiotic therapy, and 48% had suffered any embolic event, 20% suffered cerebral emboli. The commonest causative organism in our series was Staphylococcus Aureus (54.1%) with 2.3% of cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…In particular, Dunne et al found a perioperative mortality of 12.9% in a series of 85 surgical patients in Perth, primarily due to ongoing sepsis. 7 In 108 patients undergoing surgical management of IE at the Princess Alexandria Hospital in Brisbane, Nayak et al, found a 30-day mortality of 6.5% in a cohort, where the majority of patients underwent surgery on an emergency basis. 6 More liberal surgical intervention in our cohort might have resulted in better results for the whole cohort at the expense of exemplary surgical results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Dunne et al found a perioperative mortality of 12.9% in a series of 85 surgical patients in Perth, primarily due to ongoing sepsis. 7 In 108 patients undergoing surgical management of IE at the Princess Alexandria Hospital in Brisbane, Nayak et al, found a 30-day mortality of 6.5% in a cohort, where the majority of patients underwent surgery on an emergency basis. 6 More liberal surgical intervention in our cohort might have resulted in better results for the whole cohort at the expense of exemplary surgical results.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3 Although the large International Collaboration on Endocarditis (ICE) includes Australian data, few articles have reviewed the geographical and associated demographic features of IE within the Australian population. [4][5][6][7] The Hunter New England Local Health District (HNELHD) is a large health district comprising much of the northern and eastern aspect of New South Wales, Australia. It provides care for a population of 840 000 within an area of 132 845 km 2 , with a large tertiary teaching hospital in Newcastle, John Hunter Hospital, at the centre of specialist treatment.…”
Section: Introductionmentioning
confidence: 99%
“…If the infection is restricted to the valve tissue, mortality ranges between 10 and 16% (17) . Age over 65 years, preoperative inotropic requirement, uncontrolled sepsis, left side endocarditis and cerebral embolization have been found to be significantly associated with increased mortality (14) . Yankah et al reported a survival rate of 70.4±3.6% in a 17-year follow-up which stabilizes during the follow-up after the fourth year (46) .…”
Section: Resultsmentioning
confidence: 99%
“…IE is an uncommon disease that, as stated, carries significant morbidity and mortality and has a wide range of presentations (12) . Aortic valve IE frequency ranges between 36% to 50% (13)(14)(15) and IE of the mitral valve is observed between 34% to 42% (14)(15)(16)(17) according to several studies.…”
Section: Introductionmentioning
confidence: 95%
“…Average 5-year survival after cured NVA fluctuates among researchers between 75% and 88% [ 10 , 12 , 41 ]. In PVE 5-year survival is 59% to 82% [ 12 , 41 , 43 , 49 ].…”
Section: Resultsmentioning
confidence: 99%